A collar lemma for partially hyperconvex surface group representations - Beyrer, Jonas; Pozzetti, Maria Beatrice (Transactions of the American Mathematical Society, 2021)
We show that a collar lemma holds for Anosov representations of fundamental groups of surfaces into S⁢L⁡(n,R) that satisfy partial hyperconvexity properties inspired from Labourie’s work. This is the case for several open sets of Anosov representations not contained in higher rank Teichmüller spaces, as well as for Θ-positive representations into S⁢O⁡(p,q) if p≥4. We moreover show that ‘positivity properties’ known for Hitchin representations, such as being positively ratioed and having positive eigenvalue ratios, also hold for partially hyperconvex representations.